SOME LEADERSHIP STYLES AND THEIR IMPACT ON ACHIEVING HAPPINESS IN THE WORKPLACE: AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF TEACHERS AT THE UNIVERSITY OF MOSUL - Maysoon Abdullah Ahmed (Scholars Digest Publishing, 2023)
The current research aims to reveal the impact of some leadership styles (persuasive leadership, empowering leadership, narcissistic leadership, toxic leadership) on achieving happiness in the workplace with its dimensions (job satisfaction, work attachment, emotional well-being). In order to achieve the goal of the research, the (analytical descriptive) approach was adopted in presenting intellectual frameworks, data processing, analysis and interpretation, after the research community was identified in several colleges affiliated with the University of Mosul, and a sample of teachers (286) teachers was selected as a representative sample of its total community. And through the use of the statistical package (AMOS V.24), the applied side of the research was completed. So that the research reached a set of conclusions, the most important of which is the presence of a significant impact on empowerment and narcissistic and toxic leadership in achieving happiness in the workplace so the research presents a set of recommendations representing the most important of them. Among them is the need to give employees a kind of freedom and independence, which increases their sense of confidence in performing the work required of them, and thus increases their satisfaction and participation in that work. From the point of view of the employees, giving them the freedom to carry out the tasks assigned to them increases their sense of comfort with themselves and the work and makes the work environment attractive to them and not obnoxious, as freedom is an essential component in all aspects of life and not at work.
Keywords: persuasive leadership, empowering leadership, narcissistic leadership, toxic leadership, happiness in the workplace.